Russia-China Relations: An Asymmetrical Partnership? - Sergei Lukonin (Vestnik MGIMO-Universiteta)
Due to the breakdown in relations between Russia and major Western countries, Moscow is compelled to take extraordinary measures to reorient its political, trade, and economic ties. Due to its large and diversified economy and geographical proximity, China is increasingly becoming Russia's primary partner. Therefore, assessing the main outcomes of Russian-Chinese cooperation in trade, finance, economics, and science is crucial while identifying their achievements and probable limitations for further development. China has been Russia's largest trading partner for over a decade, importing mainly mineral products while exporting advanced technical products. In 2022, statistics indicate that the roles of Russia and China in bilateral trade have remained unchanged. China has further solidified its position as Russia's primary supplier of high-tech equipment, while Russia continues to be one of China's primary sources of gas and oil. China accounts for around 20% of the total foreign trade volume of the Russian Federation, while Russia's share in Chinese foreign trade turnover is about 3%. Although evaluating mutual direct and accumulated investments is challenging, it can be argued that China is among Russia's largest investors, whereas Russia's direct and accumulated investments in China, while likely higher than official estimates, are still relatively insignificant. The scope of cooperation between the Russian Federation and the People's Republic of China in the scientific and technological sectors is narrowing, although additional incentives for expansion have emerged amid the heightened USChinese strategic rivalry and the crisis between Russia and the West. Russian-Chinese cooperation in the financial sector has had some successes, primarily the expansion of the use of national currencies in bilateral trade. However, this expansion is significantly limited by anti-Russian sanctions. In the current international climate, Russian-Chinese relations have the potential to deepen, but doing so will necessitate the creation of various mechanisms that enable large Chinese companies to avoid secondary sanctions.